Feedforward modulation for the neutral-point-clamped converter with confined capacitor voltage ripples and reduced switching power losses - Beniwal, Neha (2020)
This paper presents a new modulation technique with feedforward compensation for the three-phase three-level neutral-point-clamped converter. With the proposed technique, the capacitor voltage ripples are allowed to vary within certain limits. This enables an optimised design of the converter since the maximum capacitor voltages are predefined. Furthermore, the proposed modulation technique is able to reduce switching power losses compared to modulation techniques that eliminate capacitor voltage ripples completely. The proposed technique is therefore a trade-off solution between aforementioned techniques and traditional modulation techniques where the capacitor voltage ripples are not limited. In the proposed technique, if the capacitor voltages are within the tolerable specified range, all the phases switch in two consecutive voltage levels in steady state. When the capacitor voltages go beyond the specified limits, one of the three phases is chosen to switch in three levels to inject an appropriate neutral point current for capacitor voltage balance. As the capacitor voltages are allowed to oscillate, the modulation technique is provided with feedforward compensation to avoid producing low frequency distortion on the output voltages of the converter. Experimental results are presented operating under different loading conditions.